Efektivitas Permainan Scrabble Dalam Mengukur Kemampuan Kosakata Bahasa Indonesia Anak Kelas 1 SD Insan Mulia - Lies Dharjati; Rohimah Nurul Bayyinah; Mulyani, Ani Sri; Rojak, Johan (MURABBI, 2023)
This study aims to determine the mastery of Indonesian vocabulary in grade 1 elementary school children including the quantity of vocabulary variety, word classes, and vocabulary scope. The method used is descriptive qualitative research method. The results of this study include the quantity of various Indonesian vocabulary in each child that differs from one another, nouns are the class of words that are most mastered by children, and the scope of children's vocabulary is mostly still at the level of objects, activities, situations, and things. - Other matters of a concrete nature.